2021
DOI: 10.2340/00015555-3833
|View full text |Cite
|
Sign up to set email alerts
|

Microbiome Profile in Patients with Adult Balanoposthitis: Relationship with Redundant Prepuce, Genital Mucosa Physical Barrier Status and Inflammation

Abstract: Balanoposthitis is a common inflammatory condition of male genitalia, while the overall microbiota spectrum and its relevance to contributing factors have yet to be determined. This case-control study included patients with balanoposthitis ( n = 26) and matched healthy controls ( n = 29), both uncircumcised. Overt fungal infection in balanoposthitis was excluded, swab samples were collected, 16S rRNA gene sequenced and analysed. The profile of the microbiome was fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 33 publications
2
8
0
1
Order By: Relevance
“…Our study is the first of which we are aware to analyze the tissue-level microbiome of the foreskin. Consistent with previous reports using penile swabs (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)47), the bacteria we identified are predominated by taxa commonly colonizing the skin (chiefly Corynebacteria spp) in addition to anaerobic bacteria such as Prevotella, Dialister, Murdochiella, Peptoniphilus, and Negativicoccus. These species have been associated with increased inflammation and HIV acquisition in uncircumcised men (8) and bacterial vaginosis in women (48).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our study is the first of which we are aware to analyze the tissue-level microbiome of the foreskin. Consistent with previous reports using penile swabs (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)47), the bacteria we identified are predominated by taxa commonly colonizing the skin (chiefly Corynebacteria spp) in addition to anaerobic bacteria such as Prevotella, Dialister, Murdochiella, Peptoniphilus, and Negativicoccus. These species have been associated with increased inflammation and HIV acquisition in uncircumcised men (8) and bacterial vaginosis in women (48).…”
Section: Discussionsupporting
confidence: 91%
“…While condom use, pre-exposure prophylaxis (PrEP), and medical penile circumcision are effective at reducing HIV incidence in men, the contribution of the penile microbiome to these mechanisms has not been fully explored. Previous work has shown a predominance of anaerobic species in the microbiota of swabs taken from the coronal sulcus or urethra (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11) and associated species such as Prevotella with increased mucosal inflammation, HIV target cell density and risk of HIV acquisition (4,12). Following circumcision, the surface microbiota shifts to be dominated by more aerobic species as found on other skin surfaces (6,13,14).…”
Section: Introductionmentioning
confidence: 99%
“…In previous studies, decreased hydration of the mucosa of the glans and an increased pH were found in patients with balanoposthitis. Additionally, the balanoposthitis was associated with impairment of the physical barrier provided by the male genital mucosa and a higher colonization rate of Staphylococcus warneri and Prevotella bivia [ 20 ]. Therefore, a possible treatment regimen for balanoposthitis may include restoration of both the genital mucosa barrier and the balance of the indigenous microbial population [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the balanoposthitis was associated with impairment of the physical barrier provided by the male genital mucosa and a higher colonization rate of Staphylococcus warneri and Prevotella bivia [ 20 ]. Therefore, a possible treatment regimen for balanoposthitis may include restoration of both the genital mucosa barrier and the balance of the indigenous microbial population [ 20 ]. Because of limitations of our study conditions, we did not measure the mucosal pH, transepidermal water loss, or mucosal hydration in the crypts adjacent to the preputial frenulum.…”
Section: Discussionmentioning
confidence: 99%
“…The best pH conducive for Mycoplasma growth is between 7.8 and 8. 19 In canine females, the pH value in the vagina is 7.4–8.3 20 and 6.3–6.7 in prepuce of males, 21 as opposed to humans who have lower values of 5.71 in men’s prepuce 22 and 3.8–4.5 in women’s vagina. 23 The pH values of canine semen are as follows; first fraction: 6.37, second fraction: 6.37, and the third one is 7.2; 24 and human semen pH values are between 7.2 and 8.…”
Section: Introductionmentioning
confidence: 99%